The relationship between Chinese expatriates job satisfaction and turnover intentions: An empirical study - Yang, Kun (Auckland University of Technology, 2004)
The high expatriate turnover experienced by multinational corporations (MNCs) has long been observed throughout the literature. Many factors have been identified to explain expatriate failure. Various facets of job satisfaction, among many other factors, have received the most attention from researchers. While there are numerous studies which identify the relationship between job satisfaction and turnover, there is still considerable controversy about how job satisfaction affects expatriate turnover decision. Moreover, as much of the previous research mainly focused on domestic turnover, the turnover research in an international context has had less attention. Today, Chinese have become the largest non-European, non-Maori ethnic community in New Zealand, yet little research has been conducted regarding Chinese expatriates’ job satisfaction and turnover intentions while they are on foreign assignments. Given the importance of these two concepts to an organization’s success, the purpose of this study was to explore the relationship between job satisfaction and turnover intentions among Chinese expatriate employees while they are on foreign assignment in New Zealand. Demographic factors were also investigated for their effects on turnover intentions. The results suggest that Chinese expatriates, across all industries, are generally satisfied with their current job in New Zealand and show very low turnover intentions compared to the widely reported international turnover rate. Several demographic variables (income, marital status, educational level, managerial position and tenure) are identified as being significantly related to propensity to leave among Chinese expatriates. However, the relationships between age, gender and turnover intentions lacked empirical support in this study. Due to the size and the unique nature of the sample, the generalization of the findings to other contexts needs cautious consideration. However, this study revealed some implications for international human resource practices, particularly for Chinese expatriates working in western countries.
Keywords: Job satisfaction -- New Zealand; Labor turnover -- New Zealand; Chinese -- New Zealand -- Social conditions